MARKETING TOOLS FOR REGULATING THE DOMESTIC PLANT PROTECTION PRODUCTS MARKET UNDER EUROPEAN INTEGRATION CONDITIONS (INNOVATIVE ECONOMY, 2026)
Korchynska O.A.  MARKETING TOOLS FOR REGULATING THE DOMESTIC PLANT PROTECTION PRODUCTS MARKET UNDER EUROPEAN INTEGRATION CONDITIONS Purpose. The aim of the article is to analyse of marketing instruments for regulating the plant protection products market in Ukraine and to substantiate the directions of their adaptation to European standards in the context of European integration.Methodology of research. The methodological basis of the study is a systematic approach to examining marketing tools for managing the plant protection products market. The research employed methods of analysis, synthesis, comparison, generalization, and statistical and economic analysis to assess the current state, development trends, and competitive environment of the plant protection products market. Economic and logical method was applied to substantiate directions for improving marketing management.Findings. The study found that the Ukrainian plant protection products market operates under wartime, economic, and regulatory challenges that significantly affect its development. The main market problems were identified as the spread of counterfeit products, information asymmetry among market participants, and insufficient consumer awareness regarding the quality and safety of plant protection products. The expediency of applying marketing tools aimed at increasing market transparency was substantiated, including digital registries, product verification systems, reporting mechanisms, and communication platforms for interaction with consumers. A conceptual model of marketing management for the plant protection products market based on the principle of a “triple marketing dialogue” among the government, business, and society was proposed, the implementation of which will contribute to reducing product counterfeiting and adapting the industry to European standards.Originality. For the first time, a conceptual model of marketing management of the Ukrainian plant protection products market under European integration conditions has been substantiated. The model is based on the principle of a “triple marketing dialogue” (B2G–B2B–B2C) and integrates the Marketing Transparency System (MTS) as a central regulatory mechanism. The theoretical interpretation of information asymmetry in the pesticide market as a marketing root cause of counterfeit product dissemination has been further developed, allowing anti-counterfeiting activities to be considered an independent marketing task with its own set of instruments.Practical value. The proposed conceptual model of marketing management can be used by the Ministry of Agrarian Policy and Food of Ukraine as a methodological basis for developing sectoral programs for the development of the plant protection products market and for supporting the implementation of Law No. 2775-IX through marketing mechanisms. The set of tools within the Marketing Transparency System may be introduced by state regulatory authorities as a practical mechanism for combating counterfeit products. The research findings may also be incorporated into educational programs of higher education institutions specializing in agriculture and economics within courses such as “Agrifood Market Marketing” and “Environmental Marketing”.Key words: pesticide market, plant protection products, marketing tools, European integration, market regulation, environmental marketing, agricultural market.
Keywords: pesticide market; plant protection products; marketing tools; European integration; market regulation; environmental marketing; agricultural market